Atrial natriuretic peptide in stable and decompensated chronic obstructive pulmonary disease. Issue 7 (July 1993) - Skwarski, K; Lee, M; Turnbull, L; MacNee, W
Abstract : BACKGROUND–Plasma levels of atrial natriuretic peptide (ANP) are elevated in patients with chronic obstructive pulmonary disease (COPD) and may have a role in preventing oedema formation in these patients. METHODS–Plasma ANP levels were measured in 60 patients with COPD and these measurements were related to pulmonary haemodynamics, response to treatment during exacerbations, and clinical patterns of the stable disease. RESULTS–Plasma ANP levels did not correlate significantly with right atrial or pulmonary arterial pressures but did correlate significantly with both the right ventricular end diastolic volume and right ventricular wall volume measured by magnetic resonance imaging. Oxygen (2 1/min by nasal prongs for 30 minutes) did not change the mean pulmonary arterial pressure or the level of plasma ANP. In 20 patients with an acute exacerbation of COPD plasma ANP levels were higher in those with oedema (302 (185) pg/ml) than in those without oedema (87 (43) pg/ml). Oxygen given for one hour had no effect on plasma levels of ANP. However, plasma ANP levels fell over the first three days during treatment in those with oedema, the fall correlating with the change in body weight. In a further 20 stable patients with hypoxic COPD, those with hypercapnia and previous episodes of oedema had higher levels of plasma ANP (120 (50) pg/ml) than normocapnic patients with no previous oedema (54 (15) pg/ml). CONCLUSIONS–The level of ANP is high in the plasma of patients with COPD, particularly during exacerbations in those with oedema. The association of a high plasma ANP level and volume overload is shown by the fall in ANP levels with treatment of the oedema, and the correlation between levels of ANP and right ventricular end diastolic or wall volumes.